SANKSI PIDANA LINGKUNGAN TERHADAP PERUSAHAAN YANG MELAKUKAN DUMPING LIMBAH B3 TANPA IZIN (STUDI KASUS PUTUSAN NEGERI SURABAYA NO. 109/PID.B/LH/2020/PN.SBY) - Hughes Ramadinda Etnneji; Mella Ismelina F. Rahayu (Fakultas Hukum Universitas Tarumanagara, 2021)
As the environment is one of the ecosystems that must be maintained, therefore the existence of the environment must be protected, especially for the order of living things. However, cases of B3 waste pollution that damage the environment, cases of illegal disposal of B3 waste in Indonesia often appear. One of them is B3 waste which at PT. Gunawan Fajar. How are environmental criminal sanctions against companies that violate B3 waste dumping and how are criminal sanctions applied in the Surabaya District Decision Case No. 109/Pid.B/LH/2020/PN.Sby is the problem under study. The research method used in this study is a supporting normative legal research method which was analyzed qualitatively. The results of the study describe criminal sanctions against companies that dump B3 Waste and the application of criminal sanctions in the Decision Case, namely in criminal sanctions against companies that dump B3 Waste taking into account “Article 104 of Law Number 32 of 2009 concerning Environmental Protection and Management”, and In the application of criminal sanctions to the Decision Case, it should also pay attention to “Article 102 jo 103 of Law Number 32 of 2009, Government Regulation No. 101 of 2014” concerning Management of Hazardous and Toxic Waste, as well as the theory of punishment, because this is considered too light for the Defendant.